Detection of post-F1 fish hybrids in broodstock using molecular markers: Approaches for genetic management in aquaculture - Hashimoto, Diogo Teruo [UNESP]; Prado, Fernanda Dotti do [UNESP]; Senhorini, José Augusto; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Hindawi, 2013)
Herein, we have developed molecular markers for nuclear genes to use in multiplex-PCR and PCR-RFLP, with the goal of characterising hybrid lines derived from crosses between pintado Pseudoplatystoma corruscans and cachara P. reticulatum. These markers, together with others described previously, were used to perform molecular identification analyses as genetic subsidies for Brazilian aquaculture. These analyses were performed due to the problems of high mortality in the offspring reported by the aquaculturist. From a total of 16 broodstock samples, 13 were genetically identified as hybrids; surprisingly, nine of these hybrids were found to be post-F1 lineages. These data show that the fertility of these animals can seriously affect the cultivated stocks, thus causing financial damage in this aquaculture system. The establishment of PCR-RFLP and multiplex-PCR as molecular techniques allows for both the correct management of these animals and the routine monitoring of production and trade of fish hybrids in aquaculture. Consequently, such tools will enable a sustainable development in the aquaculture industry. © 2012 Blackwell Publishing Ltd.
Keywords: Genetic identification; Hybridization; Pseudoplatystoma; Sustainable development; aquaculture industry; aquaculture production; biomarker; brood stock; economic impact; gene expression; hyaloclastite; hybrid; hybridization; molecular analysis; mortality; polymerase chain reaction; sustainable development; Brazil; Animalia; Pseudoplatystoma corruscans